A male congenital pelvic arteriovenous malformation diagnosed by abdominal ultrasound: A case report and literature review - Huang, Yanhua; Liu, Xiatian; Qian, Hongwei (Frontiers in Surgery, 2023)
Congenital pelvic arteriovenous malformation (AVM) is a rare vascular abnormality whereby arteries and veins are directly connected with malformed vascular plexus. Owing to its low incidence and nonspecific symptoms, the ultrasonographic characteristics of congenital pelvic AVM in males have been infrequently studied. A 30-year-old man visited our hospital complaining of progressive pain in the right lower abdomen and lumbar area since 2 months previously. Abdominal ultrasound (US) was performed at the initial examination and pelvic AVM was diagnosed, which was then confirmed by computed tomographic angiography. After right internal iliac artery embolization, the patient recovered uneventfully and remained asymptomatic during the 12-month follow-up period. Congenital pelvic AVM should thus be included in the differential diagnosis of pelvic cystic masses in males despite its low incidence, with US also being of great diagnostic value. We describe the ultrasonic features of AVM in detail and hope that this study may contribute to the ultrasonic diagnosis of congenital pelvic AVM in males.